Kölcsönhatások - GÁRDONYI, Zsolt (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Interactions. Music is a very special gift from God. In my opinion, it flows through the inner world of the composer and then it is shared with others through both written, and performed forms. Many technical, formal and instrumental aspects of composition can be applied to organ improvisation especially. This is true in current as well as in older worship music. Artful music fosters cathartic experiences in the listener as he journeys through life toward his creator. My personal idea of musical composition is to accompany and enhance this spiritual pilgrimage.